“Ética, Estética y Ciudadanía”, a memorizational approach - Álvarez Rivera, Josseth (2023)
This article identifies the conceptual approach of citizenship and citizen participation present in the Citizenship Education’s curriculum of Costa Rican secondary education. To achieve this goal, it has been developed a document analysis. The process started with a general reading of the document, to establish the presence or absence of the analysis units, these allows the comprehension of the theory farther than the democratic institutional perspective. Later, it was identified the frequency of the concepts, stablished by two dimensions a theorical and a practical dimensions. This comparative process showed a memorization trend, related to citizenship and citizen participation, in the expected learning of the school curriculum.